Validation of the Chinese Version of the Self-Objectification Beliefs and Behaviors Scale - Lang, Min; Ye, Yiduo (Frontiers in Psychology, 2021)
Given the limitations of the existing tools used for measuring self-objectification in China, this study aims to validate the Chinese version of the self-objectification beliefs and behaviors scale (C-SOBBS). In this study, we first translated and culturally adopted SOBBS to the Chinese context. We conducted two wave surveys. In the first-wave survey, we recruited 331 female college students whose age ranged from 18 to 35 (Mage=20.28, SD=2.99) to complete an online survey that included demographic questions, C-SOBBS, and four other scales to assess the validity of C-SOBBS. In the second-wave survey, 76 participants who took part in the first-wave survey completed the C-SOBBS at a two-week interval for the assessment of test-retest stability. A confirmatory factor analysis was performed to validate the factor structure of the C-SOBBS. The relationship between the C-SOBBS, its factors, and four other measures demonstrated that the C-SOBBS has a convergent and discriminant validity. Furthermore, the results of hierarchical multiple regression demonstrated the C-SOBBS’s incremental validity related to the Female Questionnaire of Trait Self-Objectification and Objectified Body Consciousness-Surveillance subscale. Additionally, the internal consistency and test-retest reliability of the C-SOBBS were also verified. The results of this study demonstrate the utility of the C-SOBBS in assessing the self-objectification beliefs and behaviors of young Chinese women within the context of Chinese culture.